Early nurture epigenetically tunes the oxytocin receptor - Perkeybile, Allison M.; Carter, C. Sue; Wroblewski, Kelly L.; Puglia, Meghan H.; Kenkel, William M.; Lillard, Travis S.; Karaoli, Themistoclis; Gregory, Simon G.; Mohammadi, Niaz; Epstein, Larissa; Bales, Karen L.; Connelly, Jessica J. (Psychoneuroendocrinology, 2019)
•4 CpG sites in the Oxtr promoter region are homologous in humans and prairie voles.•Low levels of early parenting lead to high Oxtr DNA methylation in brain and blood.•High Oxtr methylation is associated with low Oxtr gene expression.•Low levels of early care lead to low OXTR density, likely via high Oxtr methylation.•Peripheral measures of Oxtr DNA methylation predict central levels. Mammalian sociality is regulated in part by the neuropeptide oxytocin. In prairie voles, subtle variation in early life experience changes oxytocin receptor-mediated social behaviors. We report that low levels of early care in voles leads to de novo DNA methylation at specific regulatory sites in the oxytocin receptor gene (Oxtr), impacting gene expression and protein distribution in the nucleus accumbens. DNA methylation state of the blood predicts expression in the brain indicating the utility of the blood as a biomarker for the transcription state of the brain. These experience-sensitive CpG sites are conserved in humans, are related to gene expression in the brain, and have been associated with psychiatric disorders and individual differences in neural response to social stimuli. These results identify a mechanism by which early care regulates later displays of typical prairie vole social behavior and suggest the potential for nurture driven epigenetic tuning of OXTR in humans.